2015
DOI: 10.1039/c4sc03268c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic circular dichroism and computational study of mononuclear and dinuclear iron(iv) complexes

Abstract: The electronic structures of mononuclear and dinuclear iron(iv) complexes are studied using magnetic circular dichroism and wavefunction-based ab initio methods, and then correlated with their similar reactivities toward H- and O-atom transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 127 publications
3
35
0
Order By: Relevance
“…The difference clearly originates from considerably higher energy of the nitrido p-orbitals than the oxo p-orbitals. Furthermore, as analyzed in our earlier work on related iron(IV)-oxo complexes, 22,50 the unpaired electron in the SOMO (π* y ) is expected to contribute positive spin density in the Fe-d yz and N-p y atomic orbitals, while negative spin density on the iron center, which reduces the total spin population, mainly stems from the spin polarization. Because in the present case, the nitrido ligand has a larger spin population than the iron center, spin polarization induces some marginal negative spin density in the Fe-d xz and -d z 2 atomic orbitals as suggested by the occupation numbers of the DOMOs (π x and σ z ) substantially deviating from their anticipated value (2), and those of the corresponding VMOs (π* x and σ* z ) considerably differing from 0.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The difference clearly originates from considerably higher energy of the nitrido p-orbitals than the oxo p-orbitals. Furthermore, as analyzed in our earlier work on related iron(IV)-oxo complexes, 22,50 the unpaired electron in the SOMO (π* y ) is expected to contribute positive spin density in the Fe-d yz and N-p y atomic orbitals, while negative spin density on the iron center, which reduces the total spin population, mainly stems from the spin polarization. Because in the present case, the nitrido ligand has a larger spin population than the iron center, spin polarization induces some marginal negative spin density in the Fe-d xz and -d z 2 atomic orbitals as suggested by the occupation numbers of the DOMOs (π x and σ z ) substantially deviating from their anticipated value (2), and those of the corresponding VMOs (π* x and σ* z ) considerably differing from 0.…”
Section: Resultsmentioning
confidence: 93%
“…49 Therefore, it is necessary to employ wave function based highly correlated CASSCF/NEVPT2 approach. In our earlier work on the spectroscopy and reactivity of high valent iron-oxo complexes, 22,50 this method has been shown to deliver reliable results not only for the ground state but also for the excited states. The balanced active space should consist of the Fe-centered 3d orbitals and their ligand centered bonding partners.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, this unusual electronic structure has profuse impacts on the HAT process . In another study, MCD and computational approaches were employed to assign the key transitions of mononuclear [Fe IV (O)L(NCMe)] 2+ , (L=tris(3,5‐dimethyl‐4‐methoxylpyridyl‐2‐methyl)amine) and dinuclear ([(L)Fe IV (O)(μ‐O)Fe IV (OH)(L)] 3+ complexes which indicated that they have interrelated electronic structures of the reactive Fe IV (O) centre (even in presence of a second iron site in the dinuclear type) which is responsible for their comparable reactivities …”
Section: Electronic Structurementioning
confidence: 99%
“…9,10,20 These findings have motivated the modelling of Fenton-like gas-phase complexes of various compositions. [21][22][23][24][25][26] Densityfunctional theory (DFT) calculations have revealed that the highly reactive high-spin (quintet) state is favoured by weak (e.g. oxygen-based) coordination environments.…”
Section: Introductionmentioning
confidence: 99%